2000
DOI: 10.1073/pnas.100101097
|View full text |Cite
|
Sign up to set email alerts
|

Selection–mutation balance in polysomic tetraploids: Impact of double reduction and gametophytic selection on the frequency and subchromosomal localization of deleterious mutations

Abstract: We modeled the behavior of recessive mutations with deleterious effects to either the sporophyte or the gametophyte, or both, in polysomic tetraploid populations by allowing for varying levels of double reduction, mutation, and self-fertilization. Double reduction causes a decrease of the equilibrium frequencies of deleterious alleles, and it has much more influence on genes subjected to gametophytic selection than on genes solely under sporophytic selection. With gametophytic selection, low frequencies of dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 46 publications
0
60
0
Order By: Relevance
“…It has been widely reported that the rate of DR is expected to increase toward the telomeres (Mather 1936;Fisher 1947;Butruille and Boiteux 2000;Stift et al 2008;Nemorin et al 2012;Zielinski and Scheid 2012), given that the probability of a crossover occurring between the centromere and a locus should increase as that locus is situated further from the centromere. Nevertheless, this has been experimentally verified only rarely.…”
Section: Dr Increases Toward the Telomeresmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely reported that the rate of DR is expected to increase toward the telomeres (Mather 1936;Fisher 1947;Butruille and Boiteux 2000;Stift et al 2008;Nemorin et al 2012;Zielinski and Scheid 2012), given that the probability of a crossover occurring between the centromere and a locus should increase as that locus is situated further from the centromere. Nevertheless, this has been experimentally verified only rarely.…”
Section: Dr Increases Toward the Telomeresmentioning
confidence: 99%
“…However, hybrid breeding depends on the production of highly homozygous inbred lines. Tetraploid potato breeding might welcome greater levels of homozygosity in a crop that is often complicated by high heterozygosity (Uitdewilligen et al 2013), as well as the potential purging effect that DR can have by exposing deleterious alleles to selection (Butruille and Boiteux 2000). DR also could speed up the accumulation of rare but favorable alleles through marker-assisted selection.…”
Section: Dr In Breedingmentioning
confidence: 99%
“…Second, the level of double reduction at a locus is linearly related to that of a linked locus by an extent depending on their recombination frequency. as cited in historical literature (Muller 1914;Mather 1935;Bailey 1961) and in more recent publications (Ronfort 1998;Butruille and Boiteux 2000) and that the maximal value of recombination frequency in autotetraploids is 0.75, at which double reduction reaches its highest frequency, rather than 0.5 as in diploid species. With the assumption of a Poisson distribution of crossovers and absence of interference in recombination, we are able to work out a mapping function that is analogous to Haldane's mapping function in autotetraploid species as…”
Section: Properties Of the Two-locus Tetrasomic Modelmentioning
confidence: 87%
“…We demonstrate that the upper limits for the coefficient of double reduction and the recombination frequency are 1 4 and 3 4 , respectively. Butruille and Boiteux (2000) showed that a level of double reduction as small as 0.04 was able to reduce greatly the equilibrium frequencies of gametophytic lethal alleles. Given that the upper limit is much greater than the rate cited above, we may anticipate that double reduction is effective in eliminating lethal alleles along autotetraploid chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Selection might also occur on female gametes, although it would likely be different in both magnitude and character. Butruille and Boiteux (2000) present a single locus model allowing selection on both male and female gametes (different selection coefficients for each) in a tetraploid organism.…”
Section: Gametic Selectionmentioning
confidence: 99%